Differences Between Interictal and Ictal Generalized Spike-Wave Discharges in Childhood Absence Epilepsy: A MEG Study - Shi, Qi; Zhang, Tingting; Miao, Ailiang; Sun, Jintao; Sun, Yulei; Chen, Qiqi; Hu, Zheng; Xiang, Jing; Wang, Xiaoshan (Frontiers in Neurology, 2020)
Purpose: To investigate the differences between interictal and ictal generalized spike-wave discharges (GSWDs) for insights on how epileptic activity propagates and the physiopathological mechanisms underlying childhood absence epilepsy (CAE). Methods: 25 patients with CAE were studied using magnetoencephalography (MEG). MEG data was digitized at 6,000 Hz during the interictal and ictal GSWDs. GSWDs was analyzed at both neural magnetic source levels and function connectivity (FC) in multi-frequency bands: delta (1–4 Hz), theta (4–8 Hz), alpha (8–12 Hz), beta (12–30 Hz), gamma (30–80 Hz), ripple (80–250 Hz), and fast ripple (250–500 Hz). Brain FC was studied with the posterior cingulate cortex/precuneus (PCC/pC) as the seed region. Results: The magnetic source of interictal GSWDs mainly locates in the PCC/pC region at 4–8 Hz and 8–12 Hz, while that of ictal GSWDs mainly locates in the medial frontal cortex (MFC) at 80–250 Hz. There were statistically significant differences between interictal and ictal GSWDs (p < 0.05). The FC network involving the PCC/pC showed strong connections in the anterior-posterior pathways (mainly with the frontal cortex) at 80–250 Hz during ictal GSWDs, while the interictal GSWDs FC were mostly limited to the posterior cortex region. There was no significant difference in the magnetic source strength among interictal and ictal GSWDs at all bandwidths. Conclusions: There are significant disparities in the source localization and FC between interictal and ictal GSWDs. Low-frequency activation in the PCC/pC during inhibition of CAE possibly relates to the maintenance of consciousness during interictal GWSDs. High-frequency oscillations (HFOs) of the MFC during CAE may associate with the transmission of GSWDs. Weakened network connections may be in favor of preventing overexcitability and relates to the termination of CAE.